Non-FDI Capital Inflows in Low-Income Developing Countries : Catching the Wave? - Araujo, Juliana (IMF Working Papers; Working Paper ;, 2015)
Low-income countries (LIDCs) are typically characterized by intermittent and very modest access to private external funding sources. Motivated by recent developments in private flows to LIDCs this paper makes two contributions: First, it constructs a new comprehensive dataset on gross private capital flows with special focus on non-FDI flows in LIDCs. Concentrating on LIDCs and more specifically on gross non-FDI private flows is intentionally aimed at closing a gap in existing datasets where country coverage of developing economies is limited mainly to emerging markets (EMs). Second, using the new data, it identifies several shifting patterns of gross non-FDI private inflows to LIDCs. A surprising fact emerges: since the mid 2000's periods of surges in gross non-FDI private inflows in LIDCs are broadly comparable to those of EMs. Moreover, while gross non-FDI inflows to LIDCs are on average much lower than those to EMs, we show that the LIDC top quartile gross non-FDI inflow is comparable to the EM median inflow and converging to the EM top quartile inflow.